1999
DOI: 10.1055/s-1999-8832
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Fatigue, Maximum Strength an Stress Reactions of the Shoulder Musculature in Paraplegics

Abstract: In paraplegic patients, shoulder complaints attributable to muscle dysbalances arising from the particular daily form of exercise are often observed. The goal of therapy is to correct these imbalances through muscular training, whereby eccentric exercise might offer advantages due to lower fatigue with concurrent higher maximum strength. This study therefore examines muscle fatigue, maximum strength, and suitability for paraplegics of eccentric exercise of the shoulder. Muscle fatigue, isokinetic peak torque, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Manual wheelchair propulsion requires a pull-push action 38,39 , starting with a flexion movement from a retroflected shoulder position, combined with a low-grade abduction that is converted to adduction during the last part of the push phase, where there is internal rotation to the ends of the movement 39 . The aforementioned movements include concentric and eccentric muscles contractions for the frequent changes between braking and propulsion, that affect shoulder muscular strength and fatigue 17 . Eccentric exercise is considered theoretically beneficial because it requires less muscular fatigue in spite of higher maximum strength and muscle tension [40][41][42] ; additionally, overall metabolic and cardiovascular stress is lower in eccentric than in concentric forms of exercise 41 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Manual wheelchair propulsion requires a pull-push action 38,39 , starting with a flexion movement from a retroflected shoulder position, combined with a low-grade abduction that is converted to adduction during the last part of the push phase, where there is internal rotation to the ends of the movement 39 . The aforementioned movements include concentric and eccentric muscles contractions for the frequent changes between braking and propulsion, that affect shoulder muscular strength and fatigue 17 . Eccentric exercise is considered theoretically beneficial because it requires less muscular fatigue in spite of higher maximum strength and muscle tension [40][41][42] ; additionally, overall metabolic and cardiovascular stress is lower in eccentric than in concentric forms of exercise 41 .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, structural musculature damage has been found as result of eccentric exercise, that can be considerably reduced with only a single repeat 43 . Mayer et al 17 examined muscle fatigue, isokinetic peak torque and EMG activity eccentric (ecc) and concentric (conc) in 41 paraplegic subjects (13 early rehabilitants; 16 trained in wheelchair sports; 12 untrained) and they found that in eccentric exercise there was less muscle fatigue in all groups, highest ecc/conc peak torque ratio in trained subjects in all movements, followed by the untrained and early rehabilitants. The authors concluded that although the eccentric exercise requires lower muscle fatigue independent of the training status that induces structural damage and subjective pain, eccentric exercise is recommended with reservations in rehabilitation therapy and training 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies on the rehabilitation of the pathologies of the upper limbs, especially those related to the articular complex of the shoulder have been searching for the description of the most frequently used exercises according to the level of the electrical activation of the involved musculature (1)(2)(3)(4)(5) . The use of the surface electromyography as the methodology to study the shoulder exercises is justified by the need to know the muscular activity, once for that articular complex, the musculature actuates in a decisive manner to the articular stability, and therefore, to the biomechanics of that region.…”
Section: Introductionmentioning
confidence: 99%